The Impact of Language in Eradicating the Menace of Rape Against the Girl Child in Lagos State - Obadare Felicia Tomi (Saniya Institute, 2024)
This study explores the impact of language in eradicating the menace of rape against the girl child. Utilizing qualitative method, the research investigates how linguistic strategies in education, media, and policy can contribute to changing societal attitudes and reducing incidences of sexual violence. The study employed a descriptive research design of the survey type. The survey included a total of 100 respondents, consisting of 60 students from secondary schools, 10 teachers and educators, 15 media workers, and 15 policymakers and law enforcement officials. The study employed a simple random sampling technique to select the participants. The questionnaire, tagged